2020
DOI: 10.1038/s41598-020-60241-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel trigger complex that facilitates ribosome-associated quality control in mammalian cells

Abstract: Ribosome stalling triggers the ribosome-associated quality control (RQC) pathway, which targets collided ribosomes and leads to subunit dissociation, followed by proteasomal degradation of the nascent peptide. In yeast, RQC is triggered by Hel2-dependent ubiquitination of uS10, followed by subunit dissociation mediated by the RQC-trigger (RQT) complex. In mammals, ZNF598-dependent ubiquitination of collided ribosomes is required for RQC, and activating signal cointegrator 3 (ASCC3), a component of the ASCC com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 33 publications
4
72
2
Order By: Relevance
“…No effect on the RFP:GFP ratio was seen for a (K) 0 control reporter lacking the stalling sequence ( Figure 1 B, middle graph) and the effect was almost completely lost in cells knocked out for ZNF598 ( Figure 1 B, right graph). Thus, like ZNF598 ( Garzia et al., 2017 , Juszkiewicz and Hegde, 2017 , Sundaramoorthy et al., 2017 ), ASCC3 is needed to terminally abort translation at a poly(A)-mediated stall similar to other stalls ( Hashimoto et al., 2020 ).
Figure 1 ASCC Is Required for Aborting Translation at a Ribosome Stall (A) The dual-fluorescence reporter used to study translational stalling.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No effect on the RFP:GFP ratio was seen for a (K) 0 control reporter lacking the stalling sequence ( Figure 1 B, middle graph) and the effect was almost completely lost in cells knocked out for ZNF598 ( Figure 1 B, right graph). Thus, like ZNF598 ( Garzia et al., 2017 , Juszkiewicz and Hegde, 2017 , Sundaramoorthy et al., 2017 ), ASCC3 is needed to terminally abort translation at a poly(A)-mediated stall similar to other stalls ( Hashimoto et al., 2020 ).
Figure 1 ASCC Is Required for Aborting Translation at a Ribosome Stall (A) The dual-fluorescence reporter used to study translational stalling.
…”
Section: Resultsmentioning
confidence: 99%
“…Hel2 and Slh1 are therefore needed to abort translation and avoid readthrough at sites of ribosome slowing. Three of four subunits of the ASC-1 complex (ASCC) are homologous to the yeast RQT complex and seem to show similar phenotypes when disrupted in cultured cells ( Hashimoto et al., 2020 , Matsuo et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…ASCC is a conserved complex containing the ASCC3 helicase (Slh1 in yeast) involved in resolving collided ribosomes ( D'Orazio et al, 2019 ; Hashimoto et al, 2020 ; Ikeuchi et al, 2019 ; Juszkiewicz et al, 2020 ; Matsuo et al, 2017 ; Matsuo et al, 2020 ). Recent experiments suggest that by directly dissociating the lead ribosome into subunits, ASCC is the factor that irreversibly aborts translation and initiates RQC on the stalled ribosome ( Juszkiewicz et al, 2020 ; Matsuo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The steps downstream of ZNF598 are incompletely understood and appear to involve nuclease ( D'Orazio et al, 2019 ), a helicase complex ( Hashimoto et al, 2020 ; Matsuo et al, 2017 ; Sitron et al, 2017 ), and possibly ribosome rescue factors ( Tsuboi et al, 2012 ). Although the roles and order of action of these factors is only partially resolved ( Juszkiewicz et al, 2020 ; Matsuo et al, 2020 ), the requirement for ZNF598-mediated 40S ubiquitination ( Garzia et al, 2017 ; Juszkiewicz and Hegde, 2017 ; Matsuo et al, 2017 ; Sundaramoorthy et al, 2017 ) together with the specificity of ZNF598 for ribosome collisions ( Juszkiewicz et al, 2018 ) strongly argues that the collided ribosome is a key proxy of aberrant translation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a genome-wide CRISPRi screen showed that ASCC2 and ASCC3 are the two most potent modifiers of cell fitness in the presence of a translation inhibitor, suggesting that the proteins affect stalled ribosomes 22 . Indeed, ASCC3 has been suggested to resolve stalled ribosomes on poly-A sequences in a ribosome quality control pathway [23][24][25] . Likewise, its yeast homolog, Slh1p, has been implicated in ribosomeassociated quality control to prevent the accumulation of aberrant proteins 23,26,27 and in non-functional ribosomal RNA decay 28 .…”
mentioning
confidence: 99%